Efektivitas Diversi Urin pada Pasien Kanker Serviks di Rumah Sakit Tersier Semarang - Nugroho, Eriawan Agung; Setyasworo, Singgeh; Simangunsong, Ragam Pesona; Listiyanto, Yandhi Ari; Yudha, Fajar Gemilang Purna; Santosa, Ardy; Soedarso, Moh Adi; Wibisono, Dimas Sindhu; Daniswara, Nanda; Addin, Sofyan Rais (Medica Hospitalia : Journal of Clinical Medicine, 2023)
BACKGROUND: Obstructive uropathy and hydronephrosis are common complications of cervical cancer. In order to provide an alternative route due to ureteral obstruction, urinary diversion was performed. Urinary diversion procedures are a therapeutic option for obstructive uropathy but their effectiveness is remain unclear. There is limited data that support urinary diversion as a treatment of ureteral obstruction to improve overall survival and progression-free survival. AIM:  To determine the effectiveness of urinary diversion in the treatment of obstructive uropathy in cervical cancer patients. METHOD: This study is a cross sectional involved cervical cancer patients with symptoms of obstructive uropathy. Data were obtained from medical records and limited to patients admitted from May, 2020 to May, 2021. Primary outcome was urea level, creatinine level, stage of hydronephrosis and overall survival rate of patients. RESULT: A total of 100 patients were included in the study. In both groups, the mean age of study subjects was 52-53 years with stage IIIB being the most widely reported. There was an improvement in post creatinine in the urinary diversion group. There was a significant difference in post creatinine levels between the non-urine diversion and urinary diversion groups (p=0.039).The 12-month survival rate, in the non-urinary diversion group had a value of 86% while the urinary diversion group had a value of 94%. CONCLUSION: This study shows that urinary diversion procedure is effective in increasing the renal function and increasing the 12-month survival of cervical cancer patients with obstructive uropathy.